BANKING INDUSTRY IN BRAZIL: A STRATEGIC AND COMPETITIVE ANALYSIS OF PROFITABILITY AND OPERATIONAL EFFICIENCY - Almeida, Wilson de Jesus Beserra de; Andrade, Felix (Revista Valore, 2023)
This article analyzes and compares the profitability of the main Brazilian banks, highlighting the competitiveness of public banks against private banks, aiming to highlight the difference in profitability and its causes. Quantitative research was used, using secondary data obtained from the financial statements of the analyzed companies, through indicators. The analysis involves five financial institutions, in the period from 2010 to 2019, two public and three private, in view of the cut made by the research, which establishes a net profit of more than R 10 billion reais for the year 2019. It is evident that Private banks currently have better profitability and better operational efficiency than public banks, despite the better performance of public banks at the beginning of the period and strong reaction in the last years of the analysis. The study presents technical and managerial contributions to those interested in the banking sector, whether internal or external users. Keywords: Profitability; Operational efficiency; Public and private banks; Competitiveness.